Analysis of Sicantik Applications in License to Establish a Building Using Method V in DPMPTSP Kab. Karo - N P Dharshinni; Andre Tarigan; Insidini Fawwaz (Putaka Timur Publisher, 2021)
The online licensing website application at the Karo Regency Licensing Office functions as an online permit management information system for the community, but there are still many people who do not understand and do not understand how to carry out the online licensing process through the SICANTIK/DPMPPTST application. In addition, people who have opened online licensing applications experience problems because they do not know the flow, requirements, and ways to register for the online licensing process. This study uses the V model software development method in building licensing applications on the SICANTIK website. The results of the design of the online licensing management menu have added new features and menus to carry out the permit registration process for users so that the online permit management process becomes easier.